Impacts of designed vanillic acid-polymer-magnetic iron oxide nanocomposite on breast cancer cells - Farahnaz Barahuie; Dena Dorniani; Bullo Saifullah; Palanisamy Arulselvan; Mohd Zobir Hussein; Ravindran Jaganathan; Fawzi Mohamed Amin El-Fagaih; Ariyati Retno Pratiwi (Heliyon, 2024)
The engineered nano-vehicle was constructed using magnetic iron oxide nanoparticles (MIONs) and chitosan (CTS) to stabilize anticancer agent vanillic acid (VNA) which was loaded on CTS-coated MIONs nanocarrier, and more importantly, to achieve sustained VNA release and subsequent proper anticancer activity. The new thermally stable VNA-CTS- MIONs nanocomposite was spherical with a middle diameter of 6 nm and had a high drug loading of about 11.8 %. The MIONs and resulting nanocomposite were composed of pure magnetite and therefore, were superparamagnetic with saturation magnetizations of 53.3 and 45.7 emu.g−1, respectively. The release profiles of VNA from VNA-CTS-MIONs nanocomposite in different pH values were sustained and showed controlled pH-responsive delivery of the loaded VNA with 89 % and 74 % percentage release within 2354 and 4046 min at pH 5 and 7.4, respectively, as well as were in accordance with the pseudo-second-order model. The VNA-CTS-MIONs nanocomposite treatment at diverse concentrations remarkably decreased the viability and promoted ROS accumulation and apoptosis in the MDA-MB-231 breast cancer cells. Hence, it can be a propitious candidate for the management of breast cancer in the future.